Nucleotide composition bias and CpG dinucleotide content in the genomes of HIV and HTLV 1/2 - Kypr, J; Mrázek, J; Reich, J (Biochimica et biophysica acta, 1989)
Nucleotide compositions of the HIV subfamily and HTLV 1/2 genomes are strongly biased in a remarkably opposite way; HIV is adenine-rich and cytosine-poor while HTLV 1/2 is cytosine-rich and adenine-poor. In addition, the CpG dinucleotides are underrepresented in HIV but abundant in HTLV 1/2. By these two properties the genomes of HIV and HTLV 1/2 mimic an (A + T)-rich and (G + C)-rich segment of the host genome, respectively. These dramatic differences between the two human retroviruses might have evolved to direct integration of the retroviral genomes into specific segments of the human chromosomes.
Keywords: Nucleotides; zastoupení bazí; nukleotidy; adenin; Human T-lymphotropic virus 2; lidský T-lymfotropní virus 2; lidský T-lymfotropní virus 1; Human T-lymphotropic virus 1; cytidin; Cytosine; HIV; Base Composition; Cytidine; cytosin; Adenine